FUNCTIONAL ANALYSIS OF NEURODEGENERATIVE DISEASES- ASSOCIATED BDNF GENE’S POLYMORPHISMS: A BIOINFORMATIC APPROACH (Journal of Medical & Health Sciences Review, 2025)
Brain-Derived Neurotrophic Factor (BDNF) is a crucial member of the neurotrophin family that plays an essential role in the development and maintenance of the nervous system. Altered BDNF expression in the blood and central nervous system has been associated with the pathogenesis of various neurodegenerative disorders including Alzheimer's disease, Parkinson's disease, amyotrophic lateral sclerosis, Huntington's disease, multiple sclerosis, and ischemic stroke. This study aimed to identify deleterious single-nucleotide polymorphisms (SNPs) and evaluate their effects on BDNF protein function and stability. Bioinformatics tools such as SNP and GO, PolyPhen-2, PANTHER, SIFT, PHD-SNP, Predict-SNP, SNAP2, I Mutant, MUpro, and ConSurf were used to detect pathogenic variants in BDNF. The 3D structure of the wild-type and mutant BDNF protein was predicted using I-TASSER, while gene-gene and protein-protein interactions were examined using Gene MANIA and STRING databases. Our analysis identified ten pathogenic missense SNPs within the BDNF coding region (rs866172975, rs771341699, rs1590217373, rs751698045, rs758638310, rs1330439007, rs77787410, rs1852795747, rs1590215885, rs780128716) that significantly reduced protein stability and altered its structural configuration. Furthermore, the gene interaction analysis highlighted the key role of BDNF in several biological pathways and its association with other genes. These findings highlight the potential contribution of pathogenic nsSNPs in BDNF-related disorders and provide new insights into the molecular mechanisms underlying the development of neurological diseases.